EMOTIONAL SOLIDARITY IN TOURISM DEVELOPMENT: HOW POLICY AND KNOWLEDGE DRIVE SUPPORT IN GILGIT BALTISTAN, PAKISTAN - Hussain, Tajir; Azinuddin, Muaz; Mior Shariffuddin, Nur Shahirah; Set, Kalsitinoor (PLANNING MALAYSIA, 2024)
The participation of local communities is vital in developing tourism, as their attitudes and behaviours can significantly impact the growth and success of a destination. As the primary recipients of future tourism developments, the perspectives of local communities should guide the creation of sustainable policies aimed at maximising benefits and minimising negative impacts. The study examines how government policy, tourism knowledge, emotional solidarity, and support for tourism development are interrelated among the residents of Gilgit-Baltistan, Pakistan. Based on a quantitative and cross-sectional research design with two sampling stages comprising quota and purposive sampling, 216 responses from the residents of Gilgit-Baltistan were collected and analysed through Partial Least Square-Structural Equation Modeling (PLS-SEM). It was revealed that government policy and tourism knowledge influence residents' welcoming nature and emotional closeness, and they contribute to their support for tourism development. The findings underscore the importance of establishing targeted and effective support systems between stakeholders to sustain the benefits of tourism development.